Prevalence and incidence of Mycobacterium tuberculosis infection in nursing students in Vitória, Espírito Santo Prevalência e incidência de infecção por Mycobacterium tuberculosis em estudantes de enfermagem de Vitória, Espírito Santo - Ethel Leonor Noia Maciel; Maria Carmen Viana; Regina Célia Gomes Zeitoune; Ilce Ferreira; Geisa Fregona; Reynaldo Dietze (Revista da Sociedade Brasileira de Medicina Tropical, 2005)
This prospective study evaluated the incidence of Mycobacterium tuberculosis infection among nursing students at the Federal University of Espírito Santo, using the purified protein derivative test. In parallel, we evaluated whether knowledge on tuberculosis transmission mechanisms had any impact on nursing students' attitudes in relation to the risk of tuberculosis infection. The incidence of tuberculin conversion was 10.5% per year (p=0.035, 95% CI = 3.63-17.43), whereas the expected conversion rate in the overall population in Brazil is 0.5% per year. These results indicate nursing students as a group at risk for TB infection. Among the risk factors studied only the use of NIOSH95 masks was associated with protection against infection (RR=0.2). Furthermore there was no statistical difference among students that PPD converted and those who remained negative regarding disease knowledge and the existence of adequate facilities for patient hospitalization. Our data reinforces the need for implementing special biosafety programs targeting this professional group. Através de estudo prospectivo, avaliou-se a incidência de infecção pelo Mycobacterium tuberculosis entre estudantes de enfermagem da Universidade Federal do Espírito Santo, usando o teste do derivado de proteína purificado. Paralelamente, avaliamos se o conhecimento sobre mecanismos de transmissão da tuberculose teve algum impacto nas atitudes dos estudantes em relação ao risco de infecção por tuberculose. A incidência da conversão tuberculínica foi de 10,5% ao ano (p=0,035, 95% CI = 3,63 - 17,43), quando a taxa de conversão para a população geral no Brasil é de 0,5% ao ano. Estes resultados indicam que os estudantes de enfermagem são um grupo de risco para infecção por tuberculose. Dentre os fatores de risco estudados somente o uso da máscara NIOSH95 estava associado à proteção contra a infecção (RR=0,2). Não houve diferença estatisticamente significativa entre os estudantes que converteram o PPD e aqueles que permaneceram negativos em relação ao conhecimento sobre tuberculose e existência de condições específicas para hospitalização dos pacientes com tuberculose. Nossos dados reforçam a necessidade de implementação programas de biosegurança especiais visando este grupo de profissionais.